Generation and evaluation of antibodies against human MGF E-peptide by reverse phase protein microarray and reverse competitive ELISA. (September 2013) - Du, Hongwu; Li, Chuanbao; Jin, Haiming; Chen, Guangyu; Xun, Yiping
Background: Since 2005, as one of prohibited substances on the Prohibited List of the World Anti-Doping Agency (WADA), the occurence of mechano growth factor (MGF) abuse in sport has likely increased. However, there is still no WADA-validated and -approved method for its detection.Results: Four polyclonal antibodies (Ab-K01, Ab-B01, Ab-B02 and Ab-K02) against MGF C-terminal peptides were generated, purified and evaluated by western blot, ELISA and reverse-phase protein microarray, respectively. It was found that all the antibodies could identify their corresponding antigen in mouse serum by reverse-phase protein microarray, in particular, Ab-K01 showed the highest affinity among them and might be a potential tool for the detection of antibody affinity. Furthermore, Ab-B01 and Ab-K01 were successfully used for the determination of MGF-40 by reverse competitive ELISA.Conclusion: The quantitative measurement of MGF-40 has laid the foundation for doping detection of MGF and further biological research on MGF.